Effects of corn processing and cattle size on total tract digestion and energy and nitrogen balance. (24th November 2021) - Petzel, Emily A; Acharya, Subash; Zeltwanger, Joshua M; Bailey, Eric A; Brake, Derek W
Abstract: This study used 18 calves (295 ± 29 kg) and 18 yearlings (521 ± 29 kg) fed whole, cracked, or steam-flaked corn (SFC ) to evaluate nutrient digestion and energy balance across different types of processed corn and sizes of cattle. Cattle were fed a diet comprised of 75% corn (dry matter [DM ]-basis) from whole, cracked, or SFC to 2.5-times maintenance energy requirements. Subsequently, cattle were placed in individual stanchions, and urine and feces were collected together with measures of gas production via indirect calorimetry. Data were analyzed using the MIXED procedure of SAS. There was no interaction between corn processing and cattle size ( P ≥ 0.40). Time spent ruminating (min/d) and rumination rate (min/kg DM intake [DMI ]) were not affected by corn processing or cattle size. The eating rate (min/kg DMI) was faster ( P < 0.01) for yearlings compared with calves. Total tract starch digestion was greatest ( P = 0.01) for cattle fed SFC (97.5%), intermediate in cattle fed cracked (92.4%), and least in cattle fed whole corn (89.5%). Dietary digestible energy and metabolizable energy (Mcal/kg DMI) were greater ( P ≤ 0.05) for cattle fed SFC compared with cracked or whole. A greater proportion of digestible energy was lost to heat production ( P = 0.01) in cattle fed whole corn compared with cracked and tended to be greater ( P = 0.08) in cattle fed SFC than cracked. Conversion of digestible energy to metabolizable energy in this study was more closely related to a dynamic model used to estimate metabolizable energy of feeds to dairy cows than to a linear model used to predict metabolizable energy of feeds to beef cattle. If library estimates of net energy for maintenance are correct, then retained energy (Mcal/d) should have been similar between each type of processed corn; however, retained energy was greater ( P < 0.01) for cattle fed cracked compared with whole corn and tended to be greater ( P = 0.06) compared with SFC. Yet, observed amounts of net energy based on measures of retained energy were not different ( P ≥ 0.60) between cracked and SFC. Nitrogen balance was not affected ( P ≥ 0.30) by corn processing or cattle size, although cattle fed cracked had numerically greater ( P ≤ 035) N retention. These data indicate that physical processing of corn provides greater net energy to cattle in comparison to whole corn.